DNA isolation from museum and type collection slides of microsporidia - Hylis, Miroslav; Weiser, Jaroslav; Oborník, Miroslav; Vávra, Jirí (Journal of invertebrate pathology, 2005)
DNA from 19 species of microsporidia was isolated and amplified from infected host tissue that were originally prepared between the years 1946 and 1996. The smears, on glass microscope slides, were either Giemsa-stained or unstained. Methanol-fixed, Giemsa-stained smears proved to be suitable for DNA isolation; DNA was amplified from only two of 14 unstained slides. The isolated DNA was successfully amplified in PCRs using small subunit and large subunit rDNA primers and sequenced. The high efficiency of DNA isolation demonstrates the usefulness of archival and type collection slides for some molecular biology and molecular taxonomy studies.
Keywords: Museums; odběr biologického vzorku; polymerázová řetězová reakce; protozoální DNA; DNA primery; Microsporidia; muzea; DNA Primers; časové faktory; Animals; Polymerase Chain Reaction; DNA; Specimen Handling; Time Factors; Tissue Preservation; zvířata; uchovávání tkání; DNA, Protozoan